PENGARUH MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Handayani, Indrie (Katalogis, 2015)
This research aims to investigate the effect of intellectual capital based on Value Added Intellectual Capital (VAICTM) the consists of Value Added Human Capital (VAHC), Value Added Capital Employed (VACE), and Structural Capital Value Added (SCVA) on company value measured by price to book value (PBV). Population of this research is manufacturing companies listed on Indonesia’s Exchange Market in year 2012 – 2013. Sampe collection methode is purposive sampling with some ctriteria met by 26 companies. Data used is secondary data taken from Indonesia Capital Market Directory (ICMD) 2012 – 2013. Data analysis technique is multiple linear regressions. The result indicates that intellectual capital that consists of Value Added Human Capital (VAHC), Value Added Capital Employed (VACE), and Structural Capital Value Added (SCVA) have significant effect on company value